Pemberdayaan Ekonomi Berbasis Filantropi Islam Lembaga DT Peduli : Studi Kasus Program Mustahik Mandiri - Dede Sugih Hartono; Triana Apriani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research involves the DT Peduli program in an effort to empower the community's economy through the Mustahik Mandiri program. This program combines an Islamic philanthropic approach with the principle of economic independence, aiming to improve the welfare of mustahik while breaking the cycle of dependency. The program not only provides direct and sustainable financial assistance but also provides skills training, business mentoring, and full access to various economic resources. Thus, this intervention is designed not only to meet immediate needs but also to equip mustahik with long-term capacity to develop independently. The main vision of this program is to create a socio-economic transformation, where empowered mustahik are expected to transition into muzakki in the future. This process also strengthens the value of social solidarity and the strategic role of zakat in community development. The research method used is a descriptive qualitative approach with a case study strategy. Data were collected through in-depth interviews, participant observation, and documentation of several program beneficiaries in various regions. The data obtained were then analyzed using empowerment and sustainable development theories as an interpretive framework to understand the resulting impact. The research results show that the Mustahik Mandiri program has had a positive impact, increasing the income, skills, and self-confidence of beneficiaries. Furthermore, the program has contributed to the formation of stronger social networks and the capacity of community-based small businesses. These findings confirm that the Mustahik Mandiri program can be a model for sustainable economic empowerment, with significant implications for improving community welfare and strengthening the role of zakat in national development.